Multidimensional scale of meaningful work: construction and validation - Batuchina, Aleksandra; Iždonaitė-Medžiūnienė, Inga; Lecaj, Rron (Frontiers in Psychology, 2025)
Meaningful work allows individuals to align their jobs with their personal values and passions, resulting in greater fulfillment and commitment. When work is meaningful, employees develop resiliency during challenging times, viewing challenges as opportunities rather than obstacles. However, there is no unified definition of meaningful work as different fields attribute different dimensions to the concept. Therefore, the evaluation and measure of meaningful work dimensions is important and should evolve in response to modern trends. The purpose of this paper is to introduce and validate the Multidimensional Scale for Meaningful Work. Following a structured scientific search on the acknowledged components of meaningful work, three studies were conducted on Content Validity, Response Process Validity, and Internal Structure Validity. Utilizing a mixed-methods approach, qualitative and quantitative data aided in the development and validation of this scale. The combined results of the studies showcase a unified measure assessing the five dimensions of Meaningful Work: Job Design/Environment, Meaningful Leadership, Organizational Commitment, Work and Life Balance, and Social Impact. Lastly, 80 items for all dimensions have been indicated and persevered throughout the rigorous analysis procedures. The scale provides a transformation of a subjective phenomenological concept onto quantitative measurable dimensions. Institutions that use the scale can more deeply understand their own organizational climate and intervene depending on which dimension is lacking. The scale has been designed to measure both the individual experience of the dimensions and the organizational experience.